Association between pre-pregnancy uterine volume and preterm birth in women with adenomyosis: a retrospective cohort study - Xiaohong Guan; Dan Liu; Hong Zhou; Junting Xu; Yanping Jia; Kunming Li (BMC Pregnancy and Childbirth)
Abstract Background Adenomyosis is thought to be associated with adverse perinatal outcomes. This study aimed to assess the relationship between pre-pregnancy uterine volume and preterm birth in singleton gravid women with adenomyosis. Methods We conducted a retrospective cohort study of 586 pregnant women with a singleton pregnancy between January 2014 and December 2022 who had a pre-pregnancy diagnosis of adenomyosis in Shanghai First Maternity and Infant Hospital. Multivariate logistic models were adopted to analyze the association between pre-pregnancy uterine volume and pregnancy outcomes in adenomyosis patients, including primary outcome (preterm birth) and secondary outcomes (pregnancy complications). The logistic model was performed for subgroup analysis as a sensitivity test. Results The preterm birth (PTB) rate was 15.19% (89/586). The median uterine volume in preterm birth group 108.9 cm3 (interquartile range, 91.9-119.2) was larger than that in term birth group 85.3 cm3 (interquartile range, 67.0-101.3) (P < 0.001). The incidence of pre-eclampsia or eclampsia (13.5% vs. 5.2%, P = 0.004), placental malposition (32.6% vs. 8.9%, P < 0.001), and preterm premature rupture of membrane (PPROM) (28.1% vs. 14.3%, P = 0.001) was significantly higher in the PTB group than that in the term birth group. Multivariate logistic analysis revealed that, the pre-pregnancy uterine volume of gravid women with adenomyosis was associated with preterm birth in Model I (odds ratio [OR] adj = 1.37, per 10 cm3 increase, 95% confidence interval [CI]: 1.25–1.51, P < 0.001), Model II (OR adj = 1.40, per 10 cm3 increase, 95% CI: 1.27–1.55, P < 0.001) and Model III (OR adj = 1.36, per 10 cm3 increase, 95% CI: 1.25–1.48, P < 0.001). The inflection point of the uterine volume was 89.34 cm3. Pregnant women with focal adenomyosis exhibited distinct OR compared to those with diffuse adenomyosis between uterine volume and preterm birth (OR = 1.43; 95% CI: 1.29–1.58 vs. OR = 1.10; 95% CI: 0.91–1.33, respectively; p for interaction = 0.021). Conclusions Increased pre-pregnancy uterine volume may be a potential risk factor for preterm birth in women with adenomyosis. It may provide a target for future monitoring and intervention to reduce the risk of preterm birth in women with adenomyosis.